Kinematic design of linkage-based haptic interfaces for medical applications: a review. (6th April 2021) - Torabi, Ali; Nazari, Ali A; Conrad-Baldwin, Everly; Zareinia, Kourosh; Tavakoli, Mahdi
Abstract: A haptic interface recreates haptic feedback from virtual environments or haptic teleoperation systems that engages the user's sense of touch. High-fidelity haptic feedback is critical to the safety and success of any interaction with human beings. Such interactions can be seen in haptic systems utilized in medical fields, such as for surgical training, robotic tele-surgery, and tele-rehabilitation, which require appropriate haptic interface design and control. In order to recreate high-fidelity soft and stiff contact experiences for the user in the intended application, different designs strike different trade-offs between the desirable characteristics of an interface, such as back-drivability, low apparent inertia and low friction for the best perception of small reflected forces, large intrinsic stiffness and force feedback capability for the best perception of large reflected forces, a large-enough workspace for exploring the remote or virtual environment, and the uniformity of haptic feedback and its adequate sensitivity over the workspace. Meeting all of the requirements simultaneously is impossible, and different application-driven compromises need to be made. This paper reviews how various kinematic designs have helped address these trade-offs in desired specifications. First, we investigate the required characteristics of linkage-based haptic interfaces and inevitable trade-offs between them. Then, we study the state of the art in the kinematic design of haptic interfaces and their advantages and limitations. In all sections, we consider the applications of the intended haptic interfaces in medical scenarios. Non-linkage-based haptic interfaces are also shortly discussed to show the broad range of haptic technologies in the area. The potentials of kinematic redundancy to address the design trade-offs are introduced. Current challenges and future directions of haptic interface designs for medical applications are shortly discussed, which is finally followed by the conclusion.